Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3855/jidc.2166
|View full text |Cite
|
Sign up to set email alerts
|

Enteroaggregative E. coli O104 from an outbreak of HUS in Germany 2011, could it happen again?

Abstract: Enterohaemorrhagic E. coli (EHEC) particularly O157:H7 (Sequence type 11 complex), is the best documented and most well-known of E. coli that cause diarrhoea. The importance of EHEC lies in the severity of disease. Outbreaks can infect thousands of people causing bloody diarrhoea and haemolytic uremic syndrome (HUS) that in turn can result in protracted illness or even death. The ability of EHEC to colonise the human gut is normally associated with the presence of genes from another group of diarrhoeagenic E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 65 publications
(57 reference statements)
0
42
1
2
Order By: Relevance
“…This strain was recovered from a female traveller returning from Germany who had developed hemolytic uremic syndrome and thrombotic thrombocytopenic purpura. The strain was confirmed as typical of an outbreak strain (ST678, stx-2 ositive and intimin negative) [13].…”
Section: Creation Of Reference Assemblymentioning
confidence: 89%
See 1 more Smart Citation
“…This strain was recovered from a female traveller returning from Germany who had developed hemolytic uremic syndrome and thrombotic thrombocytopenic purpura. The strain was confirmed as typical of an outbreak strain (ST678, stx-2 ositive and intimin negative) [13].…”
Section: Creation Of Reference Assemblymentioning
confidence: 89%
“…Two E. coli O104 isolates were not linked to the German outbreak and were included as comparators. Isolates were grown according to the protocol described in Chattaaway et al [13].…”
Section: Collection Of Isolatesmentioning
confidence: 99%
“…Most of them identified the presence of EAEC based on only one gene, when several should have been analysed given that EAEC strains can harbor different combinations of genes (Chattaway et al 2011). Most studies have focused on VT-producing EAEC O104:H4 from cattle; in contrast, we are aware of only one epidemiological study on sheep as potential faecal carriers of EAEC (Cassar et al 2004) and we have not found any such study on goats.…”
Section: Introductionmentioning
confidence: 72%
“…Further information can be obtained from the detailed articles by Askar et al [8], Struelens et al [9], Frank et al [4,5], Scheutz et al [10] and from the review by Chattaway et al [3].…”
Section: Epidemiologymentioning
confidence: 99%
“…It now appears both outbreaks may have been caused by the same pathogen, Escherichia coli O104:H4 [2]. Please see the review article describing in more detail the characteristics of this bacterium by Chattaway et al [3] that is available open access in this issue of JIDC. Many challenges now face epidemiologists, microbiologists and health regulatory officials in preventing and managing these and future outbreaks of STEC 0104.…”
mentioning
confidence: 99%